Ovarian thecoma- an incidental finding in a patient with UVprolapse - Rawal, Suniti; Bista, Kesang D; Gurung, Geeta; Rana, Ashma (Nepal Journal of Obstetrics and Gynaecology, 2009)
A seventy two year old postmenopausal multiparous lady who presented with III° uterovaginal prolapse was found to have a solid mass palpable through the vaginal fornices for which the vaginal procedure was deferred for abdominal hysterectomy. A solid mass resembling fibrothecoma was discovered which after histopathological examination was reported to be thecoma pointing out the importance of preoperative evaluation. Key words: post menopausal ovarian tumor, thecoma, uterovaginal prolapse with ovarian tumor doi:10.3126/njog.v1i2.2404 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 69-70 Nov-Dec 2006